Answer:
C. (-1,6,1)
Explanation:
Given the system of equation
6x−y+3z=−9 ...... 1
5x + 5y−5z = 20 ...... 2
3x−y+4z = −5 ...... 3
Reduce the equations to two variables with 2unknown
Multiply equation 3 by 2 and add to 1.
Equation 3×2; 6x−2y+8z = −10 ...... 4
Subtract 4 from 1
-y-(-2y)+3z-8z = -9-(-10)
-y+2y-5z = -9+10
y-5z = 1 ...... 5
Also multiply eqn 2 by 3 and 3 by 5
Equation 2×3; 15x+15y-15z= 60
Equation 3×5; 15x-5y+20z = -25
Subtract
15y+5y-15z-20z = 60+25
20y-35z = 85
Divide through by 5:
4y-7z = 17 ...... 6
...................................
Solve 5 and 6
y-5z = 1 ...... 5 × 4
4y-7z = 17 ...... 6 × 1
....................................
4y-20z = 4
4y-7z = 17
Subtract
-20z+7z = 4-17
-13z = -13
z = -13/-13
z = 1
Substitute z = 1 into equation 5 to get y:
From 5: y-5z = 1
y - 5(1) = 1
y-5 = 1
y = 1+5
y = 6
Substitute y = 6 and z = 1 into equation 3 to get x;
From 3: 3x−y+4z = −5
3x-6+4(1) = -5
3x -6+4 = -5
3x-2 = -5
3x = -5+2
3x = -3
x = -3/3
x = -1
Hence x = -1, y = 6 and z = 1
The correct answer is (-1, 6, 1)